The labor magistrate of the future - Virginis, José Antonio (2023)
The purpose of this paper is to propose a model of the labor judge of the future so that he can best carry out the tasks of his judicial office in the different stages of the process. It also indicates the salient characteristics of the labor judge, the events that have affected the exercise of his functions, the principles to which he must conform, his duties and obligations, his different roles, the suitability required for his function and the importance of judicial ethics. Also, the central principles of labor law that limit the work of the labor magistrate in different thematic blocks are highlighted. Finally, the salient features of the judge as director of the process are delineated, considering the type of magistrate that society demands, and the definitive model is postulated.